A Comparative Study of “Eat” Verbs used in the Passive Voice Function in Chinese, Japanese, and English - Du, Tianyi (Silva Iaponicarum, 2026)
This study investigates the role of functional verbs in expressing passive voice across Chinese, Japanese, and English, with a focus on the Chinese verb chī ( 吃 ), the Japanese verbs kuu and kurau, and the English verb eat. The hypothesis is that these verbs can convey passive meanings by shifting the subject’s role from agent to patient, even in the absence of overt passive markers. Through a syntactic and semantic analysis, this study reveals that functional verbs in all three languages can assign passive interpretations, often implying undesirable outcomes. The findings highlight the grammatical and pragmatic similarities and differences in the use of functional verbs across these languages, emphasizing their role as a cross-linguistic phenomenon. This research contributes to a deeper understanding of passive voice beyond traditional syntactic markers, offering new insights into the interaction between functional verbs and passive constructions.